Spaced out : a comprehensive guide to award winning spaces in the UK - Garmory, Nicola (Architectural Press, 2005)
This beautifully illustrated guide celebrates some of the most significant award winning public spaces in major cities in the UK and Ireland over the last ten years.Dealing with a range of contemporary and innovating designed landscapes from urban spaces to public parks, this book focuses on those that have been awarded the highest design accolade from the Royal Institute of British Architects, The Royal Town andPlanning Institute, The Landscape Institute and The Civic Trust. Focusing on designs in ten major cities, and providing a snappy synopsi.